Sectoral Contributions to Carbon Dioxide Equivalent Emissions in the Nigerian Economy - Effiong, Mfonobong O.; Okoye, Chukwuemeka U.; Nweze, Noble J. (International Journal of Energy Economics and Policy, 2019)
In line with the Intergovernmental Panel on Climate Change (IPCC), we estimate the percentage CO2-eq emissions by sector in Nigeria. In terms of its emissions, the percentage contribution of CO2, CH4 and N2O to each sector were considered using the 2006 IPCC emission calculation default taking 2012 as the base year projected to 2027. Results revealed that, fugitive emissions from oil and gas accounted for the highest contribution to CO2-eq emissions with about 75.27 percent when compared to other sectors. This is due to increased gas flaring employed to dispose of associated gas in major petroleum/oil producing areas in the country. This sector pollutes because of their technology, the remaining sectors were identified as important sectors because of the weight they have on the economy. The study suggests the need for Nigerian government to ensure the security of fuel source for power generation by mandating oil companies to channel their flared gases to power plant. Keywords: Intergovernmental Panel on Climate Change Sector Contributions, Anthropogenic Gases, Carbon Dioxide Equivalent Emissions, Projections, Nigeria JEL Classifications: C67; Q40; Q43; Q56 DOI: https://doi.org/10.32479/ijeep.8905